Governance, Integrity, and ESG in the Gulf Countries: A Dual Approach to Responsible and Irresponsible Corporate Practices - Alazab, Hani Abdelhafez; Bawaneh, Ahmad Ali Salem; Alazab, Seleen Hani Abdel Hafez (International Review of Management and Marketing, 2026)
This research looks at the effects of board attributes and corruption control on ESG performance and controversies in GCC firms using 1,487 firm-year observations between 2010 and 2023. It takes a two-fold approach by examining both positive (ESG performance) and negative (ESG controversies) aspects, as they co-exist in companies. It reveals that effective corruption control has a positive impact on ESG performance and a negative impact on controversies. Board characteristics - including diversity, independence and size - are also important for sustainability. Corruption control improves governance, reduces fraud and fosters sustainable business practices. The research provides important lessons for policymakers and business leaders in the GCC, highlighting that strong governance and transparent corporate practices are key to achieving sustainability and enhancing corporate integrity.